2018
DOI: 10.1111/jocn.14682
|View full text |Cite
|
Sign up to set email alerts
|

Dementia‐specific drug treatment in home care settings: A German multicentre study

Abstract: Aims and objectives The aim of this study was to identify and analyse factors influencing the use of drugs for dementia treatment in home care settings. Background While the number of care‐dependent people with dementia is growing, it is not clear whether their medication follows the state of the art, especially in home care settings where over two‐thirds of them are cared for in Germany. Although dementia is not curable, it is possible to reduce cognitive, behavioural and psychological symptoms of dementia wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
2
2
0
Order By: Relevance
“…For example, for individuals diagnosed with Alzheimer’s Disease and a mild to moderate cognitive impairment, the intake of Acetylcholinesterase inhibitors is recommended [ 28 ]. In the present sample, about 37% of PwD reported the intake of an anti-dementia drug, a finding in line with previous studies [ 47 , 48 ]. For example, a study on medical treatment of PwD in Germany reported 25% of ambulatory PwD receiving an anti-dementia drug, and found that this number varied depending on whether PwD were seen by a GP and specialist or solely a GP (48% versus 24.5%, respectively) [ 49 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…For example, for individuals diagnosed with Alzheimer’s Disease and a mild to moderate cognitive impairment, the intake of Acetylcholinesterase inhibitors is recommended [ 28 ]. In the present sample, about 37% of PwD reported the intake of an anti-dementia drug, a finding in line with previous studies [ 47 , 48 ]. For example, a study on medical treatment of PwD in Germany reported 25% of ambulatory PwD receiving an anti-dementia drug, and found that this number varied depending on whether PwD were seen by a GP and specialist or solely a GP (48% versus 24.5%, respectively) [ 49 ].…”
Section: Discussionsupporting
confidence: 93%
“…For example, a study on medical treatment of PwD in Germany reported 25% of ambulatory PwD receiving an anti-dementia drug, and found that this number varied depending on whether PwD were seen by a GP and specialist or solely a GP (48% versus 24.5%, respectively) [ 49 ]. Past research has consistently reported a positive association between involvement of a GP/specialist and anti-dementia drug prescription [ 48 , 50 ]. In the present study, about 10% of PwD reported the intake of an anti-dementia drug which was not in line with GDG recommendations, and almost half (44.5%) reported an intake of off-label drugs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, for individuals diagnosed with Alzheimer's Disease and a mild to moderate cognitive impairment, the intake of Acetylcholinesterase inhibitors is recommended (28). In the present sample, about 37% of PwD reported the intake of an anti-dementia drug, a nding in line with previous studies (48,49). For example, a study on medical treatment of PwD in Germany reported 25% of ambulatory PwD receiving an anti-dementia drug, and found that this number varied depending on whether PwD were seen by a GP and specialist or solely a GP (48% versus 24.5%, respectively) (50).…”
Section: Adherence To the German Dementia Guideline In Primary Caresupporting
confidence: 91%
“…For example, a study on medical treatment of PwD in Germany reported 25% of ambulatory PwD receiving an anti-dementia drug, and found that this number varied depending on whether PwD were seen by a GP and specialist or solely a GP (48% versus 24.5%, respectively) (50). Past research has consistently reported a positive association between involvement of a GP/specialist and anti-dementia drug prescription (49,51). In the present study, about 10% of PwD reported the intake of an anti-dementia drug which was not in line with GDG recommendations, and almost half (44.5%) reported an intake of off-label drugs.…”
Section: Adherence To the German Dementia Guideline In Primary Carementioning
confidence: 99%